Argentina Public Expenditure and Financial Accountability Performance Assessment Report - World Bank (World Bank, Washington, DC, 2020)
This evaluation was conducted by a World Bank (WB) cross-sectoral team and was undertaken jointly with GoA’s Ministry of Treasury (MoT) and the Federal Council of Fiscal Responsibility (FCFR) to promote full ownership by the government through an iterative consultation and validation process, both at technical and political levels. The assessment was performed in coordination with relevant development partners—the Inter-American Development Bank (IDB) and the IMF. The French Development Agency (AFD) office in Argentina was informed of the evaluation. The assessment findings show that the performance of the PFM systems at the national level are reasonably aligned with international standards and good practices.